ROLES OF DIGITAL MEDIA IN PRESERVING TRIBAL HANDICRAFTS: Received: 14th March 2023; Revised: 11th May 2023, 5th June 2023; Accepted: 11th June 2023 - Warangmata, Dolchanok (PEOPLE: International Journal of Social Sciences, 2023)
This study aims to examine the roles of digital media in reserving tribal handicrafts corresponding to the key government policy in protecting livelihoods, arts, and cultures of tribes in Thailand. The results of the study reveal that in the 21st century, digital media play a suitable role for today's society in communicating with the audience about identities of local handicrafts. The contents are, then, perceived quickly and properly. Modern media can also enrich social values, reach out a more expansive range of the audience, and harmonize the context of Thai society. We often see the tribal handicrafts as a cultural selling point in movies, animations, advertisements, games, and online applications. Involving digital media in storing the way of life as well as recording cultural patterns and stories is beneficial resulting in the intercultural media where the digital age meets unique cultures. The creativity of digital media leads to commercial values known as a creative business to reserve tribal handicrafts in society for good.